Determination of Flavonoids Content of Gringsingan Stems (Mesosphaerum suaveolens (L) Kuntze) Extracted by Microwave Assisted Extraction - Handayani, Selpida; Aminah, Aminah; Badu, Nurul Fadillah (Universitas Muslim Indonesia, 2025)
Gringsingan plant (Mesosphaerum suaveolens (L) kuntze) is an plant belonging to the lamiaceae family originating from Sinjai district, South Sulawesi. This plant is empirically used by the people of Sinjai district as a medicine to relieve stomach aches. The modern extraction method used is microwave-assisted extraction, which is an extraction method that uses microwave radiation to speed up extraction by heating the solvent quickly and efficiently. The aim of this research was to determine the value of total flavonoid content in Gringsingan (Mesosphaerum suaveolens (L) kuntze) stems extract based on microwave-assisted extraction. This research was carried out experimentally in the laboratory. The stages of this research began with preparing test samples, testing the quality of flavonoid compounds, and ended with determining the total flavonoid content of gringsingan stems, which then measured their absorption using a UV – Vis spectrophotometer. In this study, the results were obtained that the Gringsingan stem extract was positive for containing flavonoids based on identification results using the Wilstater reagent. This sample was also declared positive for containing flavonoids based on the thin layer chromathography (TLC) test using the AICI3 specific reagent. Determination of the total flavonoid content of Gringsingan stem extract based on microwave assisted extraction. Obtained was 17.949 mgQE/g.